Recent Development in Urban Polyhydroxyalkanoates Biorefineries - Kaur, Parneet; Bhola, Shivam; Kumar, Pradeep; Kumar, Vinay; Kulshreshtha, Saurabh; Sharma, Anuj; Park, Seo A.; Choi, Kwon Young (ChemBioEng Reviews, 2023)
The widespread use of plastic items and their improper disposal harms not only physical environments but also human health globally. Therefore, a bioplastic or polymer that can completely vanish from the environment is the foremost priority. Bioplastic can be manufactured using raw materials from plants, animals, and microbes. Polyhydroxyalkaonates (PHAs) is a type of bioplastic which is naturally produced by microbes and importantly biodegradable as well as biocompostable. PHA production utilizing commercial sugars is an economically cost-effective process. Due to urbanization and industrialization a huge amount of waste is generated around the world and its management is a major environmental issue. Urban wastes produced by wastewater treatment plant, agro/food-processing industries, dairy industries, and even from household uses can be an economically sustainable feedstock for the synthesis of PHAs. The current status of bioplastic around the globe is summarized, and the urban waste potential as a feedstock for advances in PHA production technology is reviewed.
Keywords: Bio-plastics; Biorefineries; Cost effective; Human health; Industrialisation; Management IS; Physical environments; Polyhydroxyalkanoates; Polyhydroxyalkaonate; Urban wastes; Bioplastic; Biorefineries; Fermentation; Polyhydroxyalkaonates; Urban waste